-6(2p+3)-8=2(3p+5)

Simple and best practice solution for -6(2p+3)-8=2(3p+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2p+3)-8=2(3p+5) equation:


Simplifying
-6(2p + 3) + -8 = 2(3p + 5)

Reorder the terms:
-6(3 + 2p) + -8 = 2(3p + 5)
(3 * -6 + 2p * -6) + -8 = 2(3p + 5)
(-18 + -12p) + -8 = 2(3p + 5)

Reorder the terms:
-18 + -8 + -12p = 2(3p + 5)

Combine like terms: -18 + -8 = -26
-26 + -12p = 2(3p + 5)

Reorder the terms:
-26 + -12p = 2(5 + 3p)
-26 + -12p = (5 * 2 + 3p * 2)
-26 + -12p = (10 + 6p)

Solving
-26 + -12p = 10 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
-26 + -12p + -6p = 10 + 6p + -6p

Combine like terms: -12p + -6p = -18p
-26 + -18p = 10 + 6p + -6p

Combine like terms: 6p + -6p = 0
-26 + -18p = 10 + 0
-26 + -18p = 10

Add '26' to each side of the equation.
-26 + 26 + -18p = 10 + 26

Combine like terms: -26 + 26 = 0
0 + -18p = 10 + 26
-18p = 10 + 26

Combine like terms: 10 + 26 = 36
-18p = 36

Divide each side by '-18'.
p = -2

Simplifying
p = -2

See similar equations:

| 2x+29=10x-67 | | 138-4x=4x+18 | | 6x+12=22-4x | | -81+9y+2=4(4y-5)-3 | | 17X^2-7X=0 | | 7(c-2)=8(c-7) | | 4(3x-1)=6+x | | 4x+26=-38+8x | | 3m^2-1=-8m | | 4+12=75-5x | | 0=-0.1x^2+3.2x-3.5 | | 4y-4=3y+5 | | -18=18(h-3) | | 12-26=8x+2 | | 118-97=35y-42y | | -X*2+16X=0 | | 61-5x=4x+15 | | 3x-7=154-4X | | -p=9 | | -30=-5(-2b) | | 8+16=5+91 | | 11-7x=143-35x | | 2r-11r=36 | | 0.9(8x+16)=1.4-(x+2) | | -51-2x=3x+24 | | -112-8x=7x+23 | | 125x^3-27= | | 6x^2+5x-25=0 | | 8y-21=5y | | 22x=15-48x^2 | | vx+w=3 | | -24=4x-8x^2 |

Equations solver categories